Pulling the devil's kingdom down : the Salvation Army in Victorian Britain - Walker, Pamela J., 1960- (University of California Press, 2001)
This work aims to emphasize how the Salvation Army entered into 19th-century urban life. It follows the movement from its Methodist roots and East London origins through its struggles with the established denominations of England, problems with the law and the media, and the public manifestations.